Exploring local and species contributions to beta diversity in a bay fish community: A baseline assessment of the Ubatumirim Bay - da Costa, João Henrique Alliprandini [UNESP]; Martins, Itamar A.; Cetra, Mauricio; Ferreira, Fabio Cop; Souza, Ursulla Pereira (FapUNIFESP (SciELO), 2024)
The organization of fish communities into habitat use groups facilitates a replicable understanding of species distribution due to the distinctive characteristics and ecological roles of these groups. Partitioning beta diversity and assessing both species contribution to beta diversity (SCBD) and local contribution to beta diversity (LCBD) can evaluate the ecological importance of each group and measure the uniqueness of each site. This study aimed to comprehend how different habitat groups within the marine fish assemblage in the Ubatumirim Bay contribute to beta diversity and to correlate the uniqueness of each sampling site to their attributes to better understand the importance of habitat use groups and the community composition variation in the bay. We sampled ichthyofauna at six locations within the bay, employing a shrimp trawl net at varying depths. We categorized the 95 identified species into five distinct habitat groups: reef-associated, pelagic-neritic, demersal, benthopelagic, and pelagic-oceanic, each with different ecological characteristics and preferences. However, no significant differences were detected in SCBD among these groups. An increase in LCBD values was observed with the decrease in mean sediment diameter, indicating a higher environmental complexity, possibly acting as an environmental filter. One of the sampled sites, Couves Island, stood out with a significantly higher LCBD value, which underscores the importance of such diverse environments in maintaining regional biodiversity. These findings can serve as a valuable baseline reference in conservation planning and management, particularly in assessing the effectiveness of the recently established Marine Environment Protection Area. For instance, comparing the current observations with future surveys could quantify the impact of this protection initiative, thus providing evidence of management efficacy and showing the potential effects of impacts (such as predatory tourism) in the Ubatumirim Bay area.
Keywords: Assemblage vulnerability; Couves Island; Environmental filtering; Marine Protected Area; Spatial scale